Vitamins and hormones. advances in research and applications - Litwack, Gerald (Vitamins and hormones, 2000)
Under the capable and qualified editorial leadership of Dr. Gerald Litwack, Vitamins and Hormones continues to publish cutting-edge reviews of interest to endocrinologists, biochemists, nutritionists, pharmacologists, cell biologists, and molecular biologists. First published in 1943, Vitamins and Hormones is the longest-running serial published by Academic Press. In the early days of the Serial, the subjects of vitamins and hormones were quite distinct. Now, new discoveries have proved that several of the vitamins function as hormones and many of the substances inferred by the title of the serial function in signal transduction processes. Accordingly, the Editor-in-Chief has expanded the scope of the serial to reflect this newer understanding of function-structure relationships in cellular communication. The Editorial Board now reflects expertise in the field of hormone action, vitamin action, X-ray crystal structure, physiology, and enzyme mechanisms.